2003
DOI: 10.1074/jbc.m303741200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Na+ Regulates Dopamine and Angiotensin II Receptors Availability at the Plasma Membrane and Their Cellular Responses in Renal Epithelia

Abstract: The balance and cross-talk between natruretic and antinatruretic hormone receptors plays a critical role in the regulation of renal Na ؉ homeostasis, which is a major determinant of blood pressure. Dopamine and angiotensin II have antagonistic effects on renal Na ؉ and water excretion, which involves regulation of the Na ؉ ,K ؉ -ATPase activity. Herein we demonstrate that angiotensin II (Ang II) stimulation of AT1 receptors in proximal tubule cells induces the recruitment of Na ؉ ,K ؉ -ATPase molecules to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 49 publications
11
92
0
Order By: Relevance
“…We have previously demonstrated that stimulation of AT1Rs induces the phosphorylation of Ser-11 and Ser-18 of NKA ␣1 and that mutation of these amino acids prevents the Ang II-dependent regulation of NKA activity (16,17). Consistent with this, Fig.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…We have previously demonstrated that stimulation of AT1Rs induces the phosphorylation of Ser-11 and Ser-18 of NKA ␣1 and that mutation of these amino acids prevents the Ang II-dependent regulation of NKA activity (16,17). Consistent with this, Fig.…”
Section: Resultssupporting
confidence: 76%
“…For this, we used the technique of plasma membrane protein biotinylation, which has been validated in several of our previous publications (16,21,24). After treatment of the cells with either PMA or Ang II, the cells were rapidly transferred to a 4°C bath, the temperature at which the plasma membrane proteins were labeled with N-hydroxysulfosuccinimide-biotin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a balance between the increase or decrease in the number of copies within the plasma membrane determines the cell Na ϩ ,K ϩ -ATPase activity. The responses to different agonists regulating the intracellular distribution of Na ϩ ,K ϩ -ATPase are tissue-specific (3), and in renal tubule cells, the direction of the physiological response (increase versus decrease) in response to hormones that influence urinary sodium excretion appears to depend largely on the concentration of intracellular sodium (4,5).…”
mentioning
confidence: 99%